Asset Misappropriation Employee Fraud: A Case Study on an Automotive Company in Indonesia - Setiawan, Nanang; Tarjo, Tarjo; Haryadi, Bambang (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 17 No 2 (2022)DO - 10.24843/JIAB.2022.v17.i02.p03, 2022)
This study is aimed to provide an exploration of asset misappropriation employee fraud and its prevention program on an automotive company in Indonesia. This study is a case study researches collecting data by document analysis and interviews with ten informants from various departments to obtain more in-depth information about the occurrence of fraud. This study found that the most popular types of fraud on automotive company are manipulation of customer account payments (lapping), embezzlement of customer deposits that are not deposited to the company (skimming) and theft of inventory. The driving factors for committing fraud are financial pressure, lifestyle extravagant, opportunities for fraud, and lack of understanding of fraudulent behavior. Employee fraud disrupts company’s operations, consumes work time and manpower, and damages the business reputation. Fraud causes the company to incur unnecessary financial losses and expenses that will affect the company's sustainability in the future. Keywords : asset misappropriation, employee fraud, automotive company